Analysis of Economic Sector Potential using the LQ and Shift Share Method in Batu Bara Regency for the 2019-2023 Period - Nurita Pasaribu; Hotman Siboro; Desry Rasmita Tarigan (International Journal of Advanced Research, 2025)
This study aims to analyze the economic sector potential in Batu Bara Regency for the period 2019-2023 using the Location Quotient (LQ) and Shift Share Analysis (SSA) methods. The main objective is to identify key base and non-base sectors that significantly contribute to regional economic growth and to understand the dynamics of structural changes in the economy. The results indicate that sectors such as agriculture, forestry, fisheries, manufacturing, construction, and trade are base sectors with dominant contributions to the local economy, while the mining and financial services sectors are categorized as non-base sectors that have shown limited development. The SSA analysis reveals that the agriculture sector holds a significant competitive advantage, while other sectors face challenges in competitiveness at the provincial and national levels. Based on these findings, it is recommended that the local government prioritize the development of base sectors through policies that support productivity, innovation, and market expansion, in order to foster sustainable economic growth.